KEPALA SEKOLAH SEBAGAI MANAJER DAN PEMIMPIN PENDIDIKAN - Muhammad Munawir Pohan (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The principal is the central figure in the improvement of the quality of education in schools. Success or failure of an educational institution, especially in the educational unit will be greatly influenced by the competence of the head of the school, Education Minister Regulation No. 13 Year 2007 on the Standards for school / madrassa confirmed that a school / madrasah principal must have five dimensions of minimum competencies, namely: personal competence, managerial, entrepreneurial, supervision, and social. Head of school / madrasah is a teacher who is assigned additional principals / madrasah that he also should have the requisite competence competence of teachers, namely: pedagogic competence, personality, social, and professional. Based on these facts, it becomes very important for the principal master the competencies of school principals in an effort to improve the quality of education in the educational unit. Hinted at by the opinion that one of the principal as educational administrators need to complete their education with knowledge leadership insights and anticipatory attitude to changes that occur in people's lives, including the development of macro-level policies. Being the change and development of the most actual today is the higher aspirations of the people for education, and the incessant demands of education policies that include improved aspects of equal opportunity, quality, efficiency and relevance.